2019
DOI: 10.1111/liv.14041
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with direct‐acting antivirals for HCV decreases but does not eliminate the risk of hepatocellular carcinoma

Abstract: Background & Aims Data from Europe and North America have been published regarding the risk of developing hepatocellular carcinoma (HCC) after treatment with direct antiviral agents (DAA). We proposed to evaluate cumulative incidence and associated risk factors for de novo HCC. Methods This was a prospective multicentre cohort study from Latin America including 1400 F1‐F4‐treated patients with DAAs (F3‐F4 n = 1017). Cox proportional regression models (hazard ratios, HR and 95% CI) were used to evaluate indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
55
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 32 publications
6
55
1
Order By: Relevance
“…A previous study on the associated factors of HCC recurrence showed that SVR 12 rate, time between the last HCC treatment and DAA therapy initiation, noncurative HCC treatment, more than one HCC treatment before DAA therapy, tumor size, LC, and AFP-L3% were relevant factors [15,20,22]. A recent study reported that patients with previous IFN experience have a high risk of de novo HCC, and the same results were found in our study [23]. As a theory supporting this result, it was estimated that this is due to the immunomodulatory and antitumor properties of IFN rather than antiviral activity alone [24].…”
Section: Discussionsupporting
confidence: 88%
“…A previous study on the associated factors of HCC recurrence showed that SVR 12 rate, time between the last HCC treatment and DAA therapy initiation, noncurative HCC treatment, more than one HCC treatment before DAA therapy, tumor size, LC, and AFP-L3% were relevant factors [15,20,22]. A recent study reported that patients with previous IFN experience have a high risk of de novo HCC, and the same results were found in our study [23]. As a theory supporting this result, it was estimated that this is due to the immunomodulatory and antitumor properties of IFN rather than antiviral activity alone [24].…”
Section: Discussionsupporting
confidence: 88%
“…The present study could shed light on the relationship between HCC and portal hypertension. A previous report showed that HCC risk after SVR is still high in the case of portal hypertension complicated with advanced fibrosis . We also previously reported that EV is the significant independent predictor of HCC .…”
Section: Discussionsupporting
confidence: 54%
“…Cumulative incidence of death, liver decompensation, LT and HCC was not compared to an untreated population, but results were alike to those published in similar studies . In a larger cohort with long‐term follow‐up, we reported a reduced incidence of HCC in HCV‐treated patients with various DDAs regimens . Also, a recent study from France showed an improvement in all evaluated clinical outcomes …”
Section: Discussionmentioning
confidence: 51%